Case Report: Fatal Complications of BK Virus-Hemorrhagic Cystitis and Severe Cytokine Release Syndrome Following BK Virus-Specific T-Cells - Holland, Elizabeth M.; Gonzalez, Corina; Levy, Elliot; Valera, Vladimir A.; Chalfin, Heather; Klicka-Skeels, Jacquelyn; Yates, Bonnie; Kleiner, David E.; Hadigan, Colleen; Dave, Hema; Shalabi, Haneen; Hickstein, Dennis D.; et al. (Frontiers in Immunology, 2021)
BK virus (BKV)-hemorrhagic cystitis (HC) is a well-known and rarely fatal complication of hematopoietic stem cell transplantation (HSCT). Treatment for BKV-HC is limited, but virus-specific T-cells (VST) represent a promising therapeutic option feasible for use posttransplant. We report on the case of a 16-year-old male with dedicator of cytokinesis 8 (DOCK8) deficiency who underwent haploidentical HSCT complicated by severe BKV-HC, catastrophic renal hemorrhage, and VST-associated cytokine release syndrome (CRS). Gross hematuria refractory to multiple interventions began with initiation of posttransplant cyclophosphamide (PT/Cy). Complete left renal arterial embolization (day +43) was ultimately indicated to control intractable renal hemorrhage. Subsequent infusion of anti-BK VSTs was complicated by CRS and progressive multiorgan failure, with postmortem analysis confirming diagnosis of hepatic sinusoidal obstruction syndrome (SOS). This case illustrates opportunities for improvement in the management of severe BKV-HC posttransplant while highlighting rare and potentially life-threatening complications of BKV-HC and VST therapy.